Vehicle criteria pollutant (PM, NOx, CO, HCs) emissions: how low should we go?. Issue 1 (December 2018) - Winkler, S.; Anderson, J.; Garza, L.; Ruona, W.; Vogt, R.; Wallington, T.
Abstract Over the past 30–40 years, vehicle tailpipe emissions of particulate matter (PM), nitrogen oxides (NOx ), carbon monoxide (CO), and hydrocarbons (HCs) have decreased significantly. Advanced emission after-treatment technologies have been developed for gasoline and diesel vehicles to meet increasingly stringent regulations, yielding absolute emission reductions from the fleet despite increased vehicle travel. As a result of mobile and stationary source emission controls, air quality has generally improved substantially in cities across the US and Europe. Emission regulations (such as Tier 3 in the US, LEV III in California, and Euro 6 rules in the EU) will lead to even lower vehicle emissions and further improvements in air quality. We review historical vehicle emission and air quality trends, discuss the future outlook for air quality, and note that modern internal combustion engine vehicles typically have lower exhaust emissions than battery electric vehicle upstream emissions. As vehicle manufacturers and city officials grapple with questions about future mobility in cities, we raise the question "how low should we go?" for future vehicle criteria emissions. The answer to this question will have profound implications for automotive and fuel companies and for the future economic and environmental health of urban areas.